Endoscopic Features of Esophageal Varices According to Japanese Description in Cirrhosis - Vedat GÖRAL; Halil DEĞERTEKİN; Fikri CANORUÇ; Kemal YILDIZ; Ender ÇOLAKOĞLU (Turkish Journal of Gastroenterology, 2020)
-